2006
DOI: 10.1203/01.pdr.0000242361.47408.51
|View full text |Cite
|
Sign up to set email alerts
|

Plasma KL-6 Predicts the Development and Outcome of Bronchopulmonary Dysplasia

Abstract: Circulating KL-6 is a specific indicator of pulmonary injury affecting the alveolar epithelium and interstitium. Our preliminary study suggested the usefulness of plasma KL-6 as a marker of bronchopulmonary dysplasia (BPD). To confirm the diagnostic value of KL-6 for BPD as well as to determine the reference range, we conducted a larger prospective study in 135 preterm infants Ͻ32 wk GA. Among the infants without oxygen dependence at a postconceptional age of 36 wk, the plasma KL-6 level showed no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…In this study cord blood KL-6 level were elevated in preterm with BPD than control so that it may has a role in early prediction and future treatment of BPD. These results were in harmony with results obtained by Kim et al, [7] and Shigemura et al, [18] proved the importance of serum KL-6 as a marker of sarcoidosis and other interstitial lung diseases. Ogihara et al, [19] reported that KL-6, a specific lung injury marker, is increased and reflects BPD disease severity.…”
Section: Discussionsupporting
confidence: 91%
“…In this study cord blood KL-6 level were elevated in preterm with BPD than control so that it may has a role in early prediction and future treatment of BPD. These results were in harmony with results obtained by Kim et al, [7] and Shigemura et al, [18] proved the importance of serum KL-6 as a marker of sarcoidosis and other interstitial lung diseases. Ogihara et al, [19] reported that KL-6, a specific lung injury marker, is increased and reflects BPD disease severity.…”
Section: Discussionsupporting
confidence: 91%
“…To clarify the effect of antenatal exposure to Ureaplasma species or other bacteria on premature lung tissue, we used KL-6 as a lung injury marker (because serum levels of KL-6 are known to increase after lung injury) correlating with the severity of respiratory distress in infants with BPD (18). Among the infants with MV ≥2 wk, the median KL-6 level in the cord blood of Ureaplasma-positive infants, was higher than in that of the bacteria-negative infants, and this difference in KL-6 levels increased time-dependently after birth (Figure 1a).…”
Section: Articlesmentioning
confidence: 99%
“…This indication of lung injury was associated with an increased severity of subsequent BPD. Because KL-6 is a mucinous glycoprotein that is expressed by alveolar type II cells and bronchiolar cells and is known to be specifically correlated with the severity of respiratory distress in infants with BPD, increased plasma KL-6 levels at birth are presumed to be due to injury in the immature lungs resulting in the subsequent development of BPD (17,18). However, we could not clarify precisely which microorganism was most likely to play a pathogenic role in the ongoing process of BPD.…”
mentioning
confidence: 99%
“…Many studies have suggested that lung inflammation is a major contributor to the pathogenesis of BPD (5,6). Various parameters of lung inflammation may be used to show lung inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Various parameters of lung inflammation may be used to show lung inflammation. However, most of them such as N-terminal propeptide of type 3 collagen, SP-A, anti-SP-A immune complexes, nitrotyrosine, soluble E-selectin, intercellular adhesion molecule-1, allantoin, and aldehydes are not specific for lung disease or are complicated to measure (6). Krebs yon den Lundgen-6 (KL-6) is a mucinlike high-molecular weight glycoprotein that is classified into cluster 9 (MUC1) of lung tumor and differentiation antigens.…”
Section: Introductionmentioning
confidence: 99%